2014
DOI: 10.3168/jds.2014-8014
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue mass in nonlactating dairy cows fed diets differing in energy density1

Abstract: Our objective was to determine dietary energy effects on feed intake, internal fat deposition, body condition score (BCS), visceral organ mass, and blood analytes in Holstein cows. Eighteen nonpregnant, nonlactating cows (BCS = 3.04 ± 0.25) were blocked based on initial BCS and were randomly assigned within each block to 2 treatments. Treatments were either high energy [HE; net energy for lactation (NEL)=1.62 Mcal/kg] or low energy (LE; NEL = 1.35 Mcal/kg) diets fed as total mixed rations for 8 wk. The LE diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 45 publications
7
71
2
2
Order By: Relevance
“…Cows that kept their BCS after calving showed a pregnancy rate of 41.6% against only 28.9% for those losing over 1 BCS point (scale of 1 to 5). Nevertheless, as shown by Drackley et al (2014), BCS may be the same between animals with high and low BW, which can confuse the interpretation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cows that kept their BCS after calving showed a pregnancy rate of 41.6% against only 28.9% for those losing over 1 BCS point (scale of 1 to 5). Nevertheless, as shown by Drackley et al (2014), BCS may be the same between animals with high and low BW, which can confuse the interpretation.…”
Section: Discussionmentioning
confidence: 96%
“…The dairy industry had traditionally adopted body condition score (BCS) to evaluate BW loss in early lactation (Wildman et al, 1982). But, more recently, Drackley et al (2014) demonstrated that BCS may lack sensitivity to detect differences in visceral fat deposition that might increase risk for peripartal diseases and disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies (He et al, 2013;Drackley et al, 2014) have been conducted to evaluate the effects of FR on maternal and fetal organ mass in dairy cows. Some studies have demonstrated that underfeeding during gestation can cause intrauterine growth restriction, which results in impaired development and potential long-term consequences (He et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because energy that cows consume in excess of their requirements must either be dissipated as heat or stored as fat, we speculated that the excess is accumulated preferentially in internal adipose tissue depots in some cows. Moderate over-consumption of energy by non-lactating cows for 57 days led to greater deposition of fat in abdominal adipose tissues (omental, mesenteric, and perirenal) than in cows fed a high-bulk diet to control energy intake to near requirements (Drackley et al, 2014). The NEFA and signaling molecules released by visceral adipose tissues travel directly to the liver, which may cause fatty liver, subclinical ketosis and secondary problems with liver function.…”
mentioning
confidence: 99%